Posthumanist Insights into the Adoption of Diffusion Dynamics in Vocational Education and Workforce Transformation - Nadig, Ranjini S; Shukla, Tanu; Nirban, Virendra Singh (Journal of Posthumanism, 2025)
Vocational education operates within dynamic socio-technical assemblages shaped by rapid technological shifts, algorithmic governance, and evolving labour market demands. Traditional, anthropocentric models of diffusion fail to account for the distributed agency across human and non-human actors. A posthumanist reconceptualization of diffusion dynamics reveals innovation as a relational, emergent process shaped by intra-actions among learners, technologies, institutional logics, and digital infrastructures. Through the development and validation of the Academia-Industry Diffusion Dynamics Scale, three key dimensions of capability: Effective Utilisation of Resources, Sensing Capabilities, and Innovativeness, are identified. These dimensions reflect how vocational institutions adapt through entangled processes rather than linear decision-making. Factor analysis confirms the co-constitutive nature of capability formation, highlighting how institutions do not merely implement innovations but are reconfigured through them. Posthumanist theory thus offers a critical framework for understanding diffusion as an ontological transformation, positioning vocational education as a site of continuous reassembly within complex human–non-human ecosystems.